2011
DOI: 10.1016/j.anr.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Fear and Self-efficacy of Turkish Patients Receiving Insulin Therapy

Abstract: The effects of experiences of frequent and severe hypoglycemia in patients with diabetes emphasize the need for programs that support diabetes-specific self-efficacy and also guide and teach hypoglycemia prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 37 publications
4
43
0
11
Order By: Relevance
“…[22] Nevertheless, although there is a consensus that self-efficacy is essential for motivation to patients in the treatment of T2DM, it is often assessed as a general measure, which may overlook its predictive usefulness. [14,23] 1.1 Significance and aim of the study Diabetes mellitus is a chronic illness, rising tide of type II diabetes and its associated complications in Egypt and requiring a lifetime self-management behavior. Because diet, physical exercise, and physical and emotional stress can affect diabetic control, patients must learn to balance these factors to avoid fluctuations in blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Nevertheless, although there is a consensus that self-efficacy is essential for motivation to patients in the treatment of T2DM, it is often assessed as a general measure, which may overlook its predictive usefulness. [14,23] 1.1 Significance and aim of the study Diabetes mellitus is a chronic illness, rising tide of type II diabetes and its associated complications in Egypt and requiring a lifetime self-management behavior. Because diet, physical exercise, and physical and emotional stress can affect diabetic control, patients must learn to balance these factors to avoid fluctuations in blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…This fear often results in missed injections and non- adherence to treatment, as patients attempt to take corrective action to avoid recurrent hypoglycemic episodes (23,28). A recent single-center survey (n=345) in Turkey showed that patients with T1DM, who had experienced severe hypoglycemia, not only had greater levels of fear and anxiety over recurrent hypoglycemia but also displayed higher treatment adherence behavior than patients with T2DM (29). This behavior may be partially attributed to the fact that patients with T1DM acknowledge that insulin treatment is indispensable for their well-being, resulting in higher levels of treatment control and self-efficacy to avoid potentially life-threatening hypoglycemic episodes than patients with T2DM.…”
Section: Dosing Irregularitiesmentioning
confidence: 99%
“…Our sample comprised two separate datasets. The first dataset was used to generate the HFS short form, and contained 487 people (71.7% with Type 1 diabetes; 47.2% women) who had fully completed the HFS-II in studies conducted in the USA (72.3%), Turkey (13.1%), and Slovenia (14.6%) [11][12][13][14][15][16]. The mean (AE SD; range) respondent age was 43.9 (AE 13.9; 15-85) years, with a mean (AE SD; range) duration of diabetes of 17.9 (AE 11.7; 0-55) years.…”
Section: Study Cohortmentioning
confidence: 99%